THE STATE OF THE AUTOMOBILE TRANSPORTATION SYSTEM DURING THE YEARS OF INDEPENDENCE - Izatillo Omonov (Innovate Conferences, 2025)
This article examines the problems and solutions in the transportation system of Uzbekistan during the years of independence, the work carried out in the field of transport and communications, the development of the Global Logistics System, and the investment policy in the transport sector in the Republic, using the example of the regions of the Fergana Valley.
Keywords: Fergana Valley, Asaka city, Khanabad, Pungon, Rezak, Chodak investment, logistics, military-strategic, convention, Nuritdin Muhitdinov, Mamajon Rakhimov.